Mono- and binuclear palladacycles via regioselective C-H bond activation: syntheses, mechanistic insights and catalytic activity in direct arylation of azoles - Pandey, Dilip K.; Khake, Shrikant M.; Gonnade, Rajesh G.; Punji, Benudhar (RSC Advances, 2015)
{Regioselective C-H bond palladation of the hybrid pincer-type ligands, 3-R2PO-C6H4-1-(CH2NPr2)-Pr-i [(POCNiPr2)-P-R2-H; R = Ph (1a)

Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Nickel-catalyzed C(2)-H arylation of indoles with aryl chlorides under neat conditions - Pandey, Dilip K.; Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2019)
Nickel-catalyzed regioselective C(2)-H arylation of indoles and pyrroles with aryl chlorides is achieved under neat conditions. This method allows the efficient coupling of diverse aryl chlorides employing a user-friendly and inexpensive Ni(OAc)(2)/dppf catalyst system at 80 degrees C. Numerous functionalities, such as halides, alkyl ether, fluoro-alkyl ether, and thioether, and substituted amines, including heteroarenes like benzothiazolyl, pyrrolyl, indolyl, and carbazolyl, are well tolerated under the reaction conditions. The preliminary mechanistic study highlights a single-electron transfer (SET) pathway for the arylation reaction.

Nickel-catalyzed C-H alkylation of indoles with unactivated alkyl chlorides: evidence of a Ni(i)/Ni(iii) pathway - Pandey, Dilip K.; Ankade, Shidheshwar B.; Ali, Abad; Vinod, C. P.; Punji, Benudhar (Chemical Science, 2019)
A mild and efficient nickel-catalyzed method for the coupling of unactivated primary and secondary alkyl chlorides with the C-H bond of indoles and pyrroles is described which demonstrates a high level of chemo and regioselectivity. The reaction tolerates numerous functionalities, such as halide, alkenyl, alkynyl, ether, thioether, furanyl, pyrrolyl, indolyl and carbazolyl groups including acyclic and cyclic alkyls under the reaction conditions. Mechanistic investigation highlights that the alkylation proceeds through a single-electron transfer (SET) process with Ni(i)-species being the active catalyst. Overall, the alkylation follows a Ni(i)/Ni(iii) pathway involving the rate-influencing two-step single-electron oxidative addition of alkyl chlorides.

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones